A strong and transparent polyvinyl alcohol composite hydrogel and preparation method thereof

By introducing cellulose nanofibers into polyvinyl alcohol hydrogels and performing radiation crosslinking and annealing treatment, the problems of low strength and poor toughness in the prior art were solved, and a strong transparent polyvinyl alcohol composite hydrogel with a tensile strength of 21.2MPa was prepared, which is suitable for high-demand tissue engineering applications.

CN118126356BActive Publication Date: 2025-03-21河南省科学院同位素研究所有限责任公司 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410376248.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-03-21
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

In the prior art, the polyvinyl alcohol hydrogel prepared by radiation has problems such as low strength, poor toughness and easy to breakage, especially the tensile strength is only 36.7kPa, which cannot meet certain applications with high requirements, such as artificial joint cartilage, etc.

Method used

By dispersing polyvinyl alcohol and cellulose nanofibers in water and mixing them, a hydrogel matrix is ​​formed by cross-linking caused by high-energy rays, and annealing is performed to improve crystallinity. Finally, hydrating in pure water is performed to prepare a strong and transparent polyvinyl alcohol composite hydrogel.

Benefits of technology

The tensile strength of the hydrogel is significantly improved to reach 21.2MPa, which enhances its toughness and mechanical properties, making it suitable for high-demand tissue engineering materials such as artificial joint cartilage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118126356B_ABST
    Figure CN118126356B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of intelligent new materials, and discloses a strong and transparent polyvinyl alcohol composite hydrogel and a preparation method thereof; the preparation method is: dispersing polyvinyl alcohol in water, stirring and heating to ≥90°C to obtain solution A; dispersing cellulose nanofibers in water to obtain solution B; mixing solution A and solution B and then irradiating to obtain a hydrogel matrix; annealing the hydrogel matrix and immersing it in water for soaking, and taking it out after the soaking is completed, so as to obtain a strong and transparent polyvinyl alcohol composite hydrogel. The present invention improves the crystallinity and greatly improves the tensile strength and toughness of the hydrogel by annealing on the basis of radiation cross-linking of polyvinyl alcohol. The preparation process is simple to operate and can be used as a candidate material for tissue engineering such as artificial joint cartilage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of intelligent new materials, and in particular to a strong and transparent polyvinyl alcohol composite hydrogel and a preparation method thereof. Background Art

[0002] Polyvinyl alcohol is a water-soluble polymer. Due to its excellent biocompatibility and non-toxicity, polyvinyl alcohol hydrogel is widely used in many fields such as bionics, sensors, actuators, tissue engineering, and drug sustained release.

[0003] Radiation is a green method for synthesizing polyvinyl alcohol hydrogels. It has fast synthesis efficiency and good gel transparency. At the same time, radiation has the effect of disinfection and sterilization, which is suitable for application in tissue engineering, medicine and other fields. However, polyvinyl alcohol hydrogels prepared by radiation have problems such as low strength, poor toughness and easy breakage. For example, the existing technology "Radiation-assistant preparation of highly conductive, transparent and self-healing hydrogels with triple-network structure" (DOI: 10.1016 / j.polymer.2020.122156) proposes to use 60 Polyvinyl alcohol / polyethylene glycol diacrylate / agar hydrogel was prepared by Coγ-ray radiation, but the tensile strength of the hydrogel material prepared by this method was only 36.7 kPa.

[0004] To this end, the present invention provides a strong and transparent polyvinyl alcohol composite hydrogel and a preparation method thereof. Summary of the invention

[0005] In order to solve the deficiencies in the above-mentioned prior art, the present invention provides a strong and transparent polyvinyl alcohol composite hydrogel and a preparation method thereof. The present invention first disperses polyvinyl alcohol and cellulose nanofibers in water respectively, mixes the two in the form of a solution, and then induces radiation crosslinking by high-energy rays to obtain a hydrogel matrix, anneals the hydrogel matrix, and then rehydrates it in pure water to finally obtain a strong and transparent polyvinyl alcohol composite hydrogel with good tensile properties and a tensile strength of up to 21.2MPa. On the basis of radiation crosslinking of polyvinyl alcohol, the present invention improves the crystallinity by annealing, greatly improves the tensile strength and toughness of the hydrogel, and the preparation process is simple to operate, and can be used as a candidate material for tissue engineering such as artificial articular cartilage.

[0006] The tough and transparent polyvinyl alcohol composite hydrogel and the preparation method thereof of the present invention are realized by the following technical scheme:

[0007] The first object of the present invention is to provide a method for preparing a tough and transparent polyvinyl alcohol composite hydrogel, comprising the following steps:

[0008] Step 1: Disperse polyvinyl alcohol in water to obtain solution A.

[0009] Step 2: Dispersing cellulose nanofibers in water to obtain solution B.

[0010] Step 3, after mixing solution A and solution B, irradiate to obtain a hydrogel matrix; wherein the irradiation source used in the irradiation treatment is 60 Co gamma rays or electron beams.

[0011] Step 4, annealing the hydrogel matrix, immersing it in water for soaking, and taking it out after soaking, so as to obtain the strong and transparent polyvinyl alcohol composite hydrogel.

[0012] Preferably, the annealing temperature of the annealing treatment is 50-110° C., and the annealing time is 1-10 hours.

[0013] Preferably, the annealing treatment is to first fix the two ends of the hydrogel matrix with a clamp and then perform stretching annealing, and the stretching deformation is 30% to 100%.

[0014] Preferably, the soaking temperature of the soaking treatment is room temperature, and the soaking time is 2 to 48 hours.

[0015] Preferably, the mass ratio of the polyvinyl alcohol in the solution A to the cellulose nanofibers in the solution B is 20:0.6-2.5.

[0016] Preferably, in the solution A, the mass fraction of polyvinyl alcohol is 8% to 25%.

[0017] Preferably, in the solution B, the mass fraction of the cellulose nanofibers is 0.1% to 1%.

[0018] Preferably, the cellulose nanofibers have a length of 400 to 1000 nm and a diameter of 5 to 10 nm.

[0019] Preferably, after the polyvinyl alcohol is dispersed in water, the temperature is raised to 90° C. under stirring, and the obtained transparent solution is the solution A.

[0020] Preferably, the radiation source used in the irradiation treatment is 60 When Coγ rays are used, the irradiation dose is 20 to 60 kGy.

[0021] Preferably, when the irradiation source used in the irradiation treatment is an electron beam, the irradiation condition is 15 to 60 kGy.

[0022] The second object of the present invention is to provide a strong and transparent polyvinyl alcohol composite hydrogel prepared by the above preparation method.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention utilizes the characteristics of cellulose nanofibers, such as high strength, high aspect ratio and good biocompatibility. Cellulose nanofibers and polyvinyl alcohol are prepared into solutions respectively and then mixed. A hydrogel precursor is initially prepared by a radiation cross-linking method. A three-dimensional network structure is formed by radiation cross-linking induced by high-energy rays. Subsequently, a stretching annealing treatment is performed to enhance the intermolecular hydrogen bonding while orienting the molecular chains along the stretching direction, thereby improving the crystallinity, constructing a second network structure, and greatly improving the mechanical strength of the polyvinyl alcohol composite hydrogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Graph showing tensile stress-strain curves of the hydrogel materials prepared in Example 2, Comparative Example 3, and Comparative Example 4 of the present invention.

[0026] Figure 2 This is a photograph of the hydrogel material prepared in Example 1.

[0027] Figure 3 This is a photo of the hydrogel material prepared in Comparative Example 2.

[0028] Figure 4 This is a photo of the hydrogel material prepared in Comparative Example 4. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below.

[0030] The present invention provides a method for preparing a tough and transparent polyvinyl alcohol composite hydrogel, comprising the following steps:

[0031] Step 1: Disperse polyvinyl alcohol in water to obtain solution A.

[0032] It should be noted that in order to improve the dispersibility of polyvinyl alcohol in the solution after the polyvinyl alcohol forms a solution form, considering that polyvinyl alcohol is insoluble in most organic solvents and slightly soluble in dimethyl sulfoxide, and considering that the purpose of preparing the composite hydrogel material of the present invention is to develop articular cartilage materials, based on considerations of human safety issues, the present invention uses water as a solvent to disperse the polyvinyl alcohol so that the polyvinyl alcohol and water form a uniform solution.

[0033] In order to ensure that polyvinyl alcohol and water can form a solution with uniform components, in a preferred embodiment of the present invention, the polyvinyl alcohol is preferably dispersed uniformly in the water by stirring, and then the temperature is continued to be raised to 90°C under the stirring effect, so that the polyvinyl alcohol and water are fully contacted at a temperature of 90°C to form a uniform solution. The stirring rate is 60 to 180 r / min, and after the temperature is raised to 90°C, the stirring is continued until the solution is in a homogeneous and transparent state, and the obtained transparent solution is the solution A.

[0034] During the research and development process of the present invention, it was found that when the polyvinyl alcohol content in solution A is less than 8%, it is difficult to form a hydrogel by irradiation; and when the polyvinyl alcohol content in solution A is greater than 25%, the solution viscosity is large, and bubbles generated by stirring are difficult to discharge, forming a large number of holes visible to the naked eye inside the hydrogel, affecting the overall performance of the material. Therefore, in a preferred embodiment of the present invention, when preparing solution A, the amount of water should not be too much or too little, and the mass fraction of polyvinyl alcohol in solution A should preferably be 8% to 25%.

[0035] Step 2: Dispersing cellulose nanofibers in water to obtain solution B.

[0036] It should be noted that since the solvent in solution B needs to be mixed with solution A in the subsequent process, based on considerations of human safety and taking into account the uniform dispersion of cellulose nanofibers, the present invention uses water as a solvent to disperse the cellulose nanofibers, so that in the subsequent processing process, the cellulose nanofibers can be fully contacted with the polyvinyl alcohol in solution A in the form of a solution.

[0037] In order to ensure that the cellulose nanofibers can be evenly dispersed in water to form a solution B with uniform components, in a preferred embodiment of the present invention, ultrasonic dispersion is used, and the ultrasonic power is 100-500W and the ultrasonic time is 10-60min.

[0038] In order to ensure the degree of crosslinking during the subsequent radiation treatment process, and thus ensure that the toughness of the polyvinyl alcohol hydrogel can be improved, the size of the cellulose nanofibers used in the present invention should not be too small or too large. In a preferred embodiment of the present invention, the length of the cellulose nanofibers is 400 to 1000 nm and the diameter is 5 to 10 nm.

[0039] During the research and development process of the present invention, it was found that when the cellulose nanofiber content in solution B is less than 0.1% or no cellulose nanofiber is added, the toughness of the polyvinyl alcohol hydrogel cannot be improved by the added cellulose nanofibers; and when the cellulose nanofiber content is greater than 1%, the solution viscosity is too large, which will also make it difficult to discharge the bubbles in the solution, affecting the performance of the formed hydrogel. Therefore, in a preferred embodiment of the present invention, when preparing solution B, the amount of water should not be too much or too little, and the mass fraction of cellulose nanofibers in solution B is preferably 0.1% to 1%.

[0040] Step 3, after mixing solution A and solution B, irradiate to obtain a hydrogel matrix; wherein the irradiation source used in the irradiation treatment is 60 Co gamma rays or electron beams.

[0041] It should be noted that in order to ensure that after solution A and solution B are mixed, the polyvinyl alcohol in solution A and the cellulose nanofibers in solution B can be cross-linked through irradiation treatment to form a hydrogel matrix with a three-dimensional network structure, in a preferred embodiment of the present invention, the mass ratio of the polyvinyl alcohol in solution A to the cellulose nanofibers in solution B is 20:0.6~2.5.

[0042] In order to ensure that solution A and solution B are mixed evenly so as to form a uniform three-dimensional network structure through irradiation treatment, in a preferred embodiment of the present invention, mixing is carried out by stirring, and the temperature during stirring treatment is 90-95°C, the stirring rate is 60-180r / min, and the stirring time is 30-120min.

[0043] In order to ensure that solution A and solution B can be cross-linked to form a hydrogel matrix with a three-dimensional network structure through irradiation treatment, the irradiation source used in the irradiation treatment is 60 Co gamma rays or electron beams. In a preferred embodiment of the present invention, the radiation source used in the irradiation treatment is 60 When Coγ rays are used, the irradiation dose is 20 to 60 kGy. In another preferred embodiment of the present invention, when the irradiation source used in the irradiation treatment is an electron beam, the irradiation condition is 15 to 60 kGy.

[0044] Step 4, annealing the hydrogel matrix, immersing it in water for soaking, and taking it out after soaking, so as to obtain the strong and transparent polyvinyl alcohol composite hydrogel.

[0045] It should be noted that, during the research and development process, the present invention found that since the present invention does not add a cross-linking agent, the cross-linking degree of the hydrogel matrix obtained by directly irradiating the mixture of solution A and solution B is relatively low; at the same time, during the radiation process, the polyvinyl alcohol in the mixture of solution A and solution B will also degrade, resulting in a decrease in molecular weight and mechanical properties. In order to improve the mechanical properties of the composite hydrogel finally obtained, the present invention anneals the hydrogel matrix obtained in the above step 3, so as to improve the crystallinity of the hydrogel material, greatly improve the tensile strength and toughness of the hydrogel material, and obtain a strong and transparent polyvinyl alcohol composite hydrogel.

[0046] In order to ensure that the annealing treatment can improve the crystallinity, tensile strength and toughness of the hydrogel material, in another preferred embodiment of the present invention, the annealing temperature of the annealing treatment is 50-110° C., and the annealing time is 1-10 h.

[0047] In order to further improve the tensile strength and toughness of the hydrogel material, in another preferred embodiment of the present invention, the two ends of the hydrogel matrix are first fixed by a clamp and then stretched and annealed, and the stretching deformation is 30% to 100%.

[0048] The present invention takes into account that the hydrogel matrix after annealing is in a dry state, and it is similar to polyvinyl alcohol plastic in a dry state. In order to restore the properties of the hydrogel, the present invention immerses the above-mentioned hydrogel material after annealing in water for immersion treatment, and the amount of water used during immersion is not limited, as long as the hydrogel material after annealing can be completely immersed in water, so that the hydrogel material after annealing is hydrated by immersion in water, so that the composite hydrogel finally obtained restores the properties of the hydrogel.

[0049] In order to ensure that the hydrogel material after annealing can recover the properties of the hydrogel through the immersion treatment, in another preferred embodiment of the present invention, the immersion temperature of the immersion treatment is room temperature and the immersion time is 2 to 48 hours.

[0050] Example 1

[0051] This embodiment provides a tough and transparent polyvinyl alcohol composite hydrogel, which is prepared by the following steps:

[0052] Step 1, preparing polyvinyl alcohol solution:

[0053] 20 g of polyvinyl alcohol was added into 80 mL of pure water, and the temperature was raised to 90° C. while stirring, and the stirring was continued until the solution was homogeneous and transparent, thereby obtaining a polyvinyl alcohol solution.

[0054] Step 2, preparing cellulose nanofiber dispersion:

[0055] 0.6 g of cellulose nanofiber dry powder was added to 99.4 mL of pure water and ultrasonically treated at an ultrasonic power of 200 W for 10 min to obtain a cellulose nanofiber dispersion.

[0056] Step 3, irradiation treatment:

[0057] The polyvinyl alcohol solution prepared in step 1 and the cellulose nanofiber dispersion prepared in step 2 are mixed evenly and then transferred to a mold. 60 The hydrogel matrix was irradiated with Coγ rays at a dose of 30 kGy.

[0058] Step 4, annealing:

[0059] The two ends of the hydrogel matrix obtained in step 3 are fixed with clamps and stretched to deform by 30%, and then annealed at 80° C. for 4 hours to obtain an annealed hydrogel material.

[0060] Step 5, soaking treatment:

[0061] The annealed hydrogel material obtained in step 4 was immersed in water at room temperature for 12 hours, and taken out after the immersion to obtain a strong and transparent polyvinyl alcohol composite hydrogel.

[0062] Example 2

[0063] This embodiment provides a tough and transparent polyvinyl alcohol composite hydrogel, which is prepared by the following steps:

[0064] Step 1, preparing polyvinyl alcohol solution:

[0065] 20 g of polyvinyl alcohol was added into 80 mL of pure water, and the temperature was raised to 90° C. while stirring, and the stirring was continued until the solution was homogeneous and transparent, thereby obtaining a polyvinyl alcohol solution.

[0066] Step 2, preparing cellulose nanofiber dispersion:

[0067] 1.2 g of cellulose nanofiber dry powder was added to 98.8 mL of pure water and ultrasonically treated at an ultrasonic power of 200 W for 20 min to obtain a cellulose nanofiber dispersion.

[0068] Step 3, irradiation treatment:

[0069] The polyvinyl alcohol solution prepared in step 1 and the cellulose nanofiber dispersion prepared in step 2 are mixed evenly and then transferred to a mold. 60 The hydrogel matrix was irradiated with Coγ rays at a dose of 30 kGy.

[0070] Step 4, annealing:

[0071] The hydrogel matrix obtained in step 3 is annealed at 80° C. for 5 h to obtain an annealed hydrogel material.

[0072] Step 5, soaking treatment:

[0073] The annealed hydrogel material obtained in step 4 was immersed in water at room temperature for 10 hours, and taken out after the immersion to obtain a strong and transparent polyvinyl alcohol composite hydrogel.

[0074] Example 3

[0075] This embodiment provides a tough and transparent polyvinyl alcohol composite hydrogel, which is prepared by the following steps:

[0076] Step 1, preparing polyvinyl alcohol solution:

[0077] 20 g of polyvinyl alcohol was added into 80 mL of pure water, and the temperature was raised to 90° C. while stirring, and the stirring was continued until the solution was homogeneous and transparent, thereby obtaining a polyvinyl alcohol solution.

[0078] Step 2, preparing cellulose nanofiber dispersion:

[0079] 1.8 g of cellulose nanofiber dry powder was added to 98.2 mL of pure water and ultrasonically treated at an ultrasonic power of 200 W for 30 min to obtain a cellulose nanofiber dispersion.

[0080] Step 3, irradiation treatment:

[0081] The polyvinyl alcohol solution prepared in step 1 and the cellulose nanofiber dispersion prepared in step 2 are mixed evenly and then transferred to a mold. 60 The hydrogel matrix was irradiated with Coγ rays at a dose of 30 kGy.

[0082] Step 4, annealing:

[0083] The two ends of the hydrogel matrix obtained in step 3 are fixed with clamps and stretched to deform by 30%, and then annealed at 90° C. for 6 hours to obtain an annealed hydrogel material.

[0084] Step 5, soaking treatment:

[0085] The annealed hydrogel material obtained in step 4 was immersed in water at room temperature for 12 hours, and taken out after the immersion to obtain a strong and transparent polyvinyl alcohol composite hydrogel.

[0086] Example 4

[0087] This embodiment provides a tough and transparent polyvinyl alcohol composite hydrogel, which is prepared by the following steps:

[0088] Step 1, preparing polyvinyl alcohol solution:

[0089] 20 g of polyvinyl alcohol was added into 80 mL of pure water, and the temperature was raised to 90° C. while stirring, and the stirring was continued until the solution was homogeneous and transparent, thereby obtaining a polyvinyl alcohol solution.

[0090] Step 2, preparing cellulose nanofiber dispersion:

[0091] 1.2 g of cellulose nanofiber dry powder was added to 98.8 mL of pure water and ultrasonically treated at an ultrasonic power of 200 W for 20 min to obtain a cellulose nanofiber dispersion.

[0092] Step 3, irradiation treatment:

[0093] The polyvinyl alcohol solution prepared in step 1 and the cellulose nanofiber dispersion prepared in step 2 are mixed evenly and then transferred to a mold. 60 The hydrogel matrix was irradiated with Coγ rays at a dose of 25 kGy.

[0094] Step 4, annealing:

[0095] The two ends of the hydrogel matrix obtained in step 3 are fixed with clamps and stretched to deform by 30%, and then annealed at 80° C. for 5 h to obtain an annealed hydrogel material.

[0096] Step 5, soaking treatment:

[0097] The annealed hydrogel material obtained in step 4 was immersed in water at room temperature for 10 hours, and taken out after the immersion to obtain a strong and transparent polyvinyl alcohol composite hydrogel.

[0098] Example 5

[0099] This embodiment provides a tough and transparent polyvinyl alcohol composite hydrogel, which is prepared by the following steps:

[0100] Step 1, preparing polyvinyl alcohol solution:

[0101] 20 g of polyvinyl alcohol was added into 80 mL of pure water, and the temperature was raised to 90° C. while stirring, and the stirring was continued until the solution was homogeneous and transparent, thereby obtaining a polyvinyl alcohol solution.

[0102] Step 2, preparing cellulose nanofiber dispersion:

[0103] 1.8 g of cellulose nanofiber dry powder was added to 98.2 mL of pure water and ultrasonically treated at an ultrasonic power of 200 W for 30 min to obtain a cellulose nanofiber dispersion.

[0104] Step 3, irradiation treatment:

[0105] The polyvinyl alcohol solution prepared in step 1 and the cellulose nanofiber dispersion prepared in step 2 are mixed evenly and then transferred to a mold. 60 The hydrogel matrix was irradiated with Coγ rays at a dose of 40 kGy.

[0106] Step 4, annealing:

[0107] The two ends of the hydrogel matrix obtained in step 3 are fixed with clamps and stretched to deform by 30%, and then annealed at 100° C. for 5 h to obtain an annealed hydrogel material.

[0108] Step 5, soaking treatment:

[0109] The annealed hydrogel material obtained in step 4 was immersed in water at room temperature for 8 hours, and taken out after the immersion to obtain a strong and transparent polyvinyl alcohol composite hydrogel.

[0110] Example 6

[0111] This embodiment provides a tough and transparent polyvinyl alcohol composite hydrogel, which is prepared by the following steps:

[0112] Step 1, preparing polyvinyl alcohol solution:

[0113] 20 g of polyvinyl alcohol was added into 80 mL of pure water, and the temperature was raised to 90° C. while stirring, and the stirring was continued until the solution was homogeneous and transparent, thereby obtaining a polyvinyl alcohol solution.

[0114] Step 2, preparing cellulose nanofiber dispersion:

[0115] 2.5 g of cellulose nanofiber dry powder was added to 97.5 mL of pure water and ultrasonically treated at an ultrasonic power of 200 W for 40 min to obtain a cellulose nanofiber dispersion.

[0116] Step 3, irradiation treatment:

[0117] The polyvinyl alcohol solution prepared in step 1 and the cellulose nanofiber dispersion prepared in step 2 are mixed evenly and then transferred to a mold. 60 The hydrogel matrix was irradiated with Coγ rays at a dose of 50 kGy.

[0118] Step 4, annealing:

[0119] The two ends of the hydrogel matrix obtained in step 3 are fixed with clamps and stretched to deform by 60%, and then annealed at 50° C. for 3 h to obtain an annealed hydrogel material.

[0120] Step 5, soaking treatment:

[0121] The annealed hydrogel material obtained in step 4 is immersed in water at room temperature for 24 hours, and taken out after immersion to obtain a strong and transparent polyvinyl alcohol composite hydrogel.

[0122] Comparative Example 1

[0123] This comparative example provides a tough and transparent polyvinyl alcohol composite hydrogel, and the difference between this comparative example and Example 1 is only that:

[0124] In this comparative example, no cellulose nanofibers were added and no annealing treatment was performed.

[0125] Comparative Example 2

[0126] This comparative example provides a tough and transparent polyvinyl alcohol composite hydrogel, and the difference between this comparative example and Example 1 is only that:

[0127] In this comparative example, no annealing treatment was performed.

[0128] Comparative Example 3

[0129] This comparative example provides a tough and transparent polyvinyl alcohol composite hydrogel, and the difference between this comparative example and Example 1 is only that:

[0130] In this comparative example, during the annealing treatment, no stretching was performed to cause deformation, that is, the amount of stretching deformation was 0.

[0131] Comparative Example 4

[0132] This comparative example provides a tough and transparent polyvinyl alcohol composite hydrogel, and the difference between this comparative example and Example 1 is only that:

[0133] In this comparative example, during the annealing treatment, no clamps were used to fix the two ends of the hydrogel matrix.

[0134] Experimental Section

[0135] (I) Tensile performance test

[0136] The present invention takes the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4 as examples, and tests the tensile strength, elongation at break and elastic modulus thereof, and the test results are as follows: Figure 1 And as shown in Table 1.

[0137] The tensile strength of the present invention is measured according to the method of GBT 1040.3-2006.

[0138] The elongation at break of the present invention is measured according to the method of GBT 1040.3-2006.

[0139] The elastic modulus of the present invention is measured according to the method of GBT 1040.3-2006.

[0140] Figure 1 is a tensile stress-strain curve of the hydrogel material prepared in Example 2, Comparative Example 4 and Comparative Example 5. Figure 1 The test results show that increasing the tensile deformation during the annealing process leads to an increase in the tensile strength and elastic modulus of the hydrogel material and a decrease in the elongation at break, because the polyvinyl alcohol molecular chains and cellulose nanofibers are oriented under the tensile stress. Comparative Example 3 only fixes the two ends of the hydrogel material without stretching it, but the stress generated by the water loss and shrinkage of the hydrogel material during the annealing process also has a stretching effect. Comparative Example 4 does not fix the hydrogel material, and there is no stretching during the annealing process.

[0141] Table 1 Test results of tensile strength, elongation at break and elastic modulus

[0142] Tensile strength / MPa Elongation at break / % Elastic modulus / MPa Example 1 20.1 400.3% 3.7 Example 2 21.2 380.4% 4.2 Example 3 18.7 379.1% 3.7 Comparative Example 1 0.017 154.3% / Comparative Example 2 0.047 165.4% / Comparative Example 3 17.7 456.6% 3.1 Comparative Example 4 15.9 580.7% 2.0

[0143] Table 1 shows the test results of tensile strength, elongation at break and elastic modulus of the hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-4. It can be seen from Table 1 that the tensile strength of the hydrogel material prepared by the method of the present invention is ≥18.7MPa, which is much greater than the prior art "Radiation-assistant preparation of highly conductive, transparent and self-healing hydrogels with triple-network structure" (DOI: 10.1016 / j.polymer.2020.122156) 60 The tensile strength (36.7 kPa) of polyvinyl alcohol / polyethylene glycol diacrylate / agar hydrogel prepared by Coγ-ray radiation indicates that the preparation method of the present invention can significantly improve the tensile strength of the hydrogel material, and the tensile strength is significantly improved compared with the prior art.

[0144] In Table 1, by comparing the test results of tensile strength, elongation at break and elastic modulus of Examples 1-3, it can be seen that the tensile strength and elastic modulus of the composite hydrogel show a trend of first increasing and then decreasing with the increase of the cellulose nanofiber content, indicating that the addition of cellulose nanofibers can improve the tensile strength and elastic modulus of the composite hydrogel, but excessive use will lead to a decrease in the effect of cellulose nanofibers on improving the tensile strength and elastic modulus of the composite hydrogel, and will cause the elongation at break of the composite hydrogel to decrease, which is consistent with the aforementioned conclusion of the present invention. The mass fraction of cellulose nanofibers in solution B is preferably 0.1% to 1%.

[0145] By comparing the test results of Example 1 with those of Comparative Example 1, it can be seen that when cellulose nanofibers are added and annealed, the tensile strength of the composite hydrogel obtained is increased by hundreds of times, and the elongation at break and elastic modulus of the composite hydrogel are also significantly improved. This indicates that the addition of cellulose nanofibers and stretching annealing treatment have an important influence on improving the tensile strength, elongation at break and elastic modulus of the composite hydrogel.

[0146] By comparing the test results of Example 1 and Comparative Example 2, it can be seen that annealing treatment has a major influence on improving the tensile strength of the composite hydrogel.

[0147] By comparing the test results of Example 1 and Comparative Example 3, it can be seen that the stretching treatment during annealing also has an important influence on further improving the tensile strength of the composite hydrogel.

[0148] By comparing the test results of Example 1 and Comparative Example 4, it can be seen that the fixing effect on both ends of the hydrogel matrix during the annealing treatment also has an important influence on further improving the tensile strength of the composite hydrogel.

[0149] By comparing the test results of Comparative Example 1 with those of Comparative Example 2, it can be seen that the addition of cellulose nanofibers can improve the tensile strength and toughness of polyvinyl alcohol hydrogel. The polyvinyl alcohol hydrogel without the addition of cellulose nanofibers will break due to excessive stress during the stretching annealing process.

[0150] Based on the above, it can be seen that the present invention increases the tensile strength of polyvinyl alcohol by hundreds of times by setting the processing steps of stretching annealing and rehydration, and at the same time, it shows a trend of first increasing and then decreasing with the increase of cellulose nanofiber content. In addition, during the annealing process, the two ends of the hydrogel are fixed before stretching, which can improve the tensile strength and elastic modulus and reduce the elongation at break.

[0151] (II) Crystallization performance test

[0152] The present invention takes the hydrogel materials prepared in Examples 3-5 and Comparative Examples 1 and 3 as examples, and tests the crystallinity thereof, and the test results are shown in Table 2.

[0153] The crystallinity of the present invention is calculated by DSC measurement according to the method in the literature (Macromolecules, 2004, 37 (25): 9510-9516. DOI: 10.1021 / ma048418v). After freeze-drying the hydrogel, 3 to 5 mg of the sample is taken for DSC test. The calculation formula is as follows:

[0154]

[0155] Where X c is the crystallinity, ΔH represents the melting enthalpy of the hydrogel, which is obtained by integrating the melting endothermic peak of the DSC curve; ΔH c The standard melting enthalpy of fully crystalline polyvinyl alcohol is fixed at 138.6 J / g.

[0156] Table 2 Crystallization performance test results

[0157] Crystallinity / % Example 3 25.8% Example 4 27.1% Example 5 24.9% Comparative Example 1 19.9% Comparative Example 3 22.6%

[0158] According to the test results in Table 2, stretching annealing can improve the crystallinity of polyvinyl alcohol hydrogel, thereby enhancing its tensile properties. The radiation dose of Example 5> the radiation dose of Example 3> the radiation dose of Example 4, which is inversely proportional to the crystallinity. The increase in radiation dose (which can also be regarded as the absorbed dose of the hydrogel material) increases the crosslinking degree, thereby reducing the crystallinity.

[0159] (III) Macroscopic morphology analysis

[0160] The present invention takes the hydrogel materials prepared in Example 1, Comparative Example 2 and Comparative Example 4 as examples, and takes photos of the macroscopic morphology of the obtained hydrogel materials. Figure 2-Figure 4 shown.

[0161] in, Figure 2 The hydrogel material prepared in Example 1 shows that the hydrogel material can remain flat except for the two ends clamped by the clamp, which is in sharp contrast to Comparative Example 4.

[0162] Figure 3 This is the hydrogel material prepared in Comparative Example 2. It can be seen that the polyvinyl alcohol / nanocellulose radiation hydrogel that has not been annealed has good transparency and a smooth surface.

[0163] Figure 4 This is the hydrogel material prepared in Comparative Example 4. It can be seen that failure to fix the edges of the hydrogel material during the annealing process will cause the material to shrink toward the center and form wrinkles, affecting subsequent applications.

[0164] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a strong and transparent polyvinyl alcohol composite hydrogel, characterized in that: The following steps are involved: Dispersing polyvinyl alcohol in water to obtain solution A; dispersing cellulose nanofibers in water to obtain solution B; After mixing solution A and solution B, irradiation treatment is performed to obtain a hydrogel matrix; wherein the irradiation source used in the irradiation treatment is 60 Co gamma rays or electron beams; After annealing the hydrogel matrix, immersing it in water for soaking, and taking it out after soaking, so as to obtain the strong and transparent polyvinyl alcohol composite hydrogel; The annealing treatment is to first fix the two ends of the hydrogel matrix with a clamp and then perform stretching annealing, and the stretching deformation is 30% to 100%; The mass ratio of the polyvinyl alcohol in the solution A to the cellulose nanofibers in the solution B is 20:0.6-2.5; In the solution A, the mass fraction of polyvinyl alcohol is 8% to 25%; In the solution B, the mass fraction of the cellulose nanofibers is 0.1% to 1%.

2. The preparation method according to claim 1, characterized in that The annealing temperature of the annealing treatment is 50-110° C., and the annealing time is 1-10 hours.

3. The preparation method according to claim 1, characterized in that: The soaking temperature of the soaking treatment is room temperature, and the soaking time is 2 to 48 hours.

4. The preparation method according to claim 1, characterized in that: After the polyvinyl alcohol is dispersed in water, the temperature is raised to 90° C. under stirring, and the obtained transparent solution is the solution A.

5. The preparation method according to claim 1, characterized in that: The radiation source used in the irradiation treatment is 60 For Coγ-ray, the irradiation dose is 20-60 kGy; When the irradiation source used in the irradiation treatment is an electron beam, the irradiation condition is 15 to 60 kGy.

6. A strong and transparent polyvinyl alcohol composite hydrogel prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Irradiation cross-linked high-light-transmittance nanocellulose / polyvinyl alcohol composite hydrogel and preparation method thereof

    CN115636955A

  • Hydrogel intelligent electronic ligament or tendon

    CN116271218A

  • Method for preparing tough hydrogel based on directional annealing casting method and application of tough hydrogel

    CN117164891A